Reconstructing Aesthetic Education Curriculum in Vocational Colleges amid Digital Transformation: Integrating Intangible Cultural Heritage and Craftsman Spirit - Wenjiang ZHANG; Wenzhou SHU (Journal of Exploration of Vocational Education, 2025)
Digital transformation and traditional culture drive the urgent need for reconstructing the aesthetic education curriculum system in vocational colleges. From an interdisciplinary perspective, this study proposes a full-chain framework: theoretical foundation, practical dilemma, path reconstruction, and safeguard mechanism. Based on embodied cognition theory and the five - education integration concept, a trinity learning scenario of "body - environment - culture" is designed. It discloses the symbiotic link between technical aesthetics and professional quality in vocational aesthetic education. Case studies show that digital resources cut the learning cycle by 40%, the 'three-dimensional coupling' system raises the job - aesthetic element match by 29%, and the 'four-stage progressive' framework helps students gain 12 innovation patents. Research offers a solution to vocational aesthetic education problems like disciplinary barriers, and provides theoretical support and practical paths for cultivating new - era vocational talents with technical aesthetics and cultural inheritance.